Learning in secondary preservice teacher education from the communities of practice perspective (2005)
On the basis of a study of a group of mathematics preservice teachers working at home developing the tasks for a methods course, we discuss the implications of introducing the communities of practice perspective in mathematics teacher education. We argue that learning as a social practice should be valued in this context and we identify some of the issues involved in designing and implementing teacher training programs based on this conceptual framework.